Preparation, characterization and stability of KF/Si-MCM-41 basic catalysts for application in soybean oil transesterification with methanol. Issue 2 (June 2015) - Ranucci, C.R.; Colpini, L.M.S.; Monteiro, M.R.; Kothe, V.; Gasparrini, L.J.; Alves, H.J.
Graphical abstract